2009
DOI: 10.1007/s11267-009-9213-2
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Photocatalytic Oxidation of Humic Acid on Anatase and Mixed-phase Anatase–Rutile TiO2 Nanoparticles

Abstract: In this study, slurry photocatalytic oxidation process was investigated for natural organic matter removal from aqueous humic acid solutions by using different titanium dioxide (TiO 2 ) under UV-A irradiation. Bench scale experimental studies were conducted at different humic acid concentration at the range of 10-50 mg/L and different pH. Anatase and mixedphase anatase-rutile TiO 2 nano particles used in the photocatalytic reactor. The results were evaluated in terms of the parameters that are specific to orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In 1976, Carey et al [2] found that after irradiated by UV light, TiO 2 was capable to catalyze the dechloridization of polychlorobiphenyl (a group of organic pollutants) in water, which initiated the application of the photocatalytic technology on environmental remediation. In the past decades, TiO 2 has been applied in decomposition and mineralization of some persistent organic pollutants (POPs) such as phenols, chlorophenols, pestcides, herbicides, benzenes, humic acids and others [3][4][5][6][7], as well as water and air purification [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Carey et al [2] found that after irradiated by UV light, TiO 2 was capable to catalyze the dechloridization of polychlorobiphenyl (a group of organic pollutants) in water, which initiated the application of the photocatalytic technology on environmental remediation. In the past decades, TiO 2 has been applied in decomposition and mineralization of some persistent organic pollutants (POPs) such as phenols, chlorophenols, pestcides, herbicides, benzenes, humic acids and others [3][4][5][6][7], as well as water and air purification [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the optimal catalyst concentration for decolorizing MB in our case study was found to be 1 g/L of P25-TiO 2 at the constant suspension flow rate of 460 mL/min using the pr-PTC. From the previous literatures on the investigation of photocatalytic water treatment in continuous flowing system, the catalyst concentrations were mostly used in the range of 0.04-0.5 g/L and not more than 2.0 g/L, as shown in Table 3 and other researches [36][37][38][39][40][41][42][43][44][45][46][47]. The optimum of P25-TiO 2 concentrations possibly depends on the suspension flow rate used in the independent system for purifying water.…”
Section: Effect Of Fluid Flow Rate On Methylene Blue Photodecolorizationmentioning
confidence: 99%
“…Although, other authors (Yigit & Inan, 2009) have provided evidence on how a mixture anatase-rutile provides a higher efficiency in humic acid mineralization.…”
Section: Introductionmentioning
confidence: 99%